Makna Perjumpaan Allah dengan Hagar dan Janda di Sarfat untuk Mengkritik Stigma tentang Janda - Ermin Alperiana Mosooli; Mardian Baali (Sekolah Tinggi Agama Kristen Luwuk Banggai, 2023)
Widows in society, in general, often receive a stigma that tends to place them as sexual objects, labelling them immoral, seductive, and dangerous because they have the potential to seize other people's husbands. Stigma limits the space for widows to move, from limited space to socialize to the difficulty of getting a job. The story of Hagar and the widow at Zarephath in the Bible illustrates God's concern for the hardships of their lives as widows. God is present in their lives and provides a way out so they can continue their lives well. This study explores the meaning of God's encounter with Hagar and the widow of Zarephath and its benefits in criticizing the stigma about widows living in society. The method used is a literature study. The results found: 1) God's encounter with Hagar and the widow of Zarephath provided a way out for both of them to get out of difficulties and continue their lives well; 2) the meaning of God's encounter with Hagar and the widow of Zarephath contradicts the stigma that exists in society about widows because stigma limits the space for widows to get out of difficulties and continue their lives.